Effect of Potential on Seepage under Dropping Hydraulic Structures (Sebha University Conference Proceedings, 2025)
Structures built on straight bottoms had design standards. However, those standards could not be utilized upon a drop hydraulic structure design. Therefore, seepage under hydraulic structures with dropping foundations have to study the seepage to be able to design against the uplift pressures that cause the structure to become unbalanced and collapse.In this study, focused on calculating the generated potential under the base of the hydraulic structure using the drag coefficients method. Moreover, the effect of the basic parameters on the potential was thoughtful. These parameters are represented by the height of the vertical drop (D) at the base of the structure and it was located (L1), as well as at the end of the structure the depth of the sheet pile (S). All variables were attributed to the length of the base of the structure (L). As that, the results of the study were highlighted through diagrams placed in a non-dimensional form for ease of use when designing dropping hydraulic structures.This study showed that the potential increases at the points (B, C, D) when the drop is at the toes point, while the potential increase is also at point D in the first and second cases by increasing the depth of the sheet pile .Through the analysis, it was found that the potential at point B increases slightly due to the increase in the drop height in the second case. While the drop is at the toes point.  The potential value increases for point B.